2018
DOI: 10.1108/jieb-05-2017-0020
|View full text |Cite
|
Sign up to set email alerts
|

The impact of social media on international student recruitment: the case of Lebanon

Abstract: PurposeThe purpose of this study is to understand and accentuate the value of social media in international student recruitment in Lebanese higher education institutions (HEIs). This study analyses the significance of social media and the changes occurring in the means of communicating with the potential international students, with an aim to understand how the HEIs could adapt with the changes to implement a model of engagement to include social media as a fundamental constituent of the Lebanese HEIs’ interna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 24 publications
1
20
0
Order By: Relevance
“…As emphasized by Cho et al (2017) the adoption of SM as a CSR communication tool is recommended, as it creates a communication environment where interactive and dialogic aspects inherently reside. Through the communication of CSR initiatives on SM platforms, firms are able to interact with a large number of stakeholders (including customers, investors, activists, employees and members of the local community) through the exchange of online visible messages initiated, created, circulated and consumed by users, can better understand consumers’ expectations, respond to criticism, and reduce scepticism contributing to creating corporate and social values (Perks et al , 2018; Dunn and Harness, 2018; Vrontis et al , 2018; Korschun and Du, 2013). This occurs because users of online communities try to affiliate themselves with virtual groups that express their values (Bagozzi and Dholakia, 2006), and when firms take responsibility for environmental, ethical, cultural or community-related issues, the users identify themselves with these issues and become themselves spokespersons for business activities, strengthening the corporate reputational capital (Isaksson et al , 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…As emphasized by Cho et al (2017) the adoption of SM as a CSR communication tool is recommended, as it creates a communication environment where interactive and dialogic aspects inherently reside. Through the communication of CSR initiatives on SM platforms, firms are able to interact with a large number of stakeholders (including customers, investors, activists, employees and members of the local community) through the exchange of online visible messages initiated, created, circulated and consumed by users, can better understand consumers’ expectations, respond to criticism, and reduce scepticism contributing to creating corporate and social values (Perks et al , 2018; Dunn and Harness, 2018; Vrontis et al , 2018; Korschun and Du, 2013). This occurs because users of online communities try to affiliate themselves with virtual groups that express their values (Bagozzi and Dholakia, 2006), and when firms take responsibility for environmental, ethical, cultural or community-related issues, the users identify themselves with these issues and become themselves spokespersons for business activities, strengthening the corporate reputational capital (Isaksson et al , 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Other studies, however, have revealed that, although international students use some SNSs for their college search activities, they prefer traditional sources of information, such as family, friends, and HEI websites, with SNSs playing a complementary role (Vrontis et al, 2018;West, 2016;Wilkins & Huisman, 2014). Similarly, a National Association of College Admission Counseling report (Clinedinst & Koranteng, 2017) did not find SNSs to be among the top recruitment strategies for domestic or international students.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Wong et al (2018) found four constructs of online university information that students perceive as important in their search behaviour: university reputation, eligibility and affordability, teaching and learning, and university tangibility. A study in Lebanon found 67 per cent of students were influenced by Facebook reviews to determine university course selection (Vrontis et al , 2018).…”
Section: Review Of Literaturementioning
confidence: 99%